Extrusion for the Sustainable Development of Novel Foods : basics, Principles, and Applications - Rolandelli, Guido; Farroni, Abel Eduardo; Buera, María del Pilar (Taylor & Francis Group, 2023)
Extrusion processing is a thermo-mechanical technology that was initially developed for the plastic industry, but then it was adapted for cereals’ food development using extruders with different lengths and diameters. During this process, the raw ingredients are fed into a cylinder, where one or two co- or counter-rotating screws mix and shear the materials through the different sections of the barrel. Extrusion flexibility and versatility allow obtaining a wide variety of products using the same technology: breakfast cereals, snacks, cereal bars, pellets, different types of pasta, texturized proteins, and meat analogues among others.